INTERACTIVE METADISCOURSE AND INTERACTIONAL METADISCOURSE CATEGORIES OF STUDENTS’ INTERNATIONAL PROGRAM SCHOOL BASED ON GENDER - suhono suhono; Haikal Haikal (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
ABSTRACTThe aim of this study was to develop further analyzing of metadiscourse categories in second language learners of International Program School of Muhammadiyah University Surakarta. Specifically, the researchers explored metadiscourse categories (interactive and Interactional) of students’ writing result at International Program of Muhammadiyah University Surakarta, the differences of metadiscourse categories with regard to gender (males and female) and factor affected metadiscourse in male and female. The researcher employed Hyland’s metadiscourse model in analyzing students’ written form which consis of 10 male and 7 female students. The results revealed that interactive metadiscourse consist of frame markers, transition markers, endophoric marker, evidendionals, and code glosses. Meanwhile, the interactional metadiscourse concist of boosters, edges, attitude markers, self-mentions and engagement markers. The researchers also revealed that the category of transition marker was the highest on female students since most female students learn at outside class such as at pondok pesantren.ABSTRAKTujuan penelitian ini adalah untuk mengembangkan analisis lebih lanjut terhadap kategori metadiscourse pada pembelajar bahasa kedua pada Program Internasional Sekolah Universitas Muhammadiyah Surakarta. Secara khusus, para peneliti mengeksplorasi kategori metadiscourse (interactive dan interactional) pada hasil tulisan mahasiswa, perbedaan kategori metadiscourse pada ”gender” (laki-laki dan perempuan) dan faktor yang mempengaruhi metadiscourse pada laki laki dan perempuan. Para peneliti menggunakan model Hyland dalam menganalisis metadiscourse pada tulisan mahasiswa yang terdiri dari 10 laki-laki dan 7 perempuan. Penelitian ini menunjukkan bahwa interactive metadiscourse terdiri dari frame markers, transition markers, endhoporic markers, evidendionals, dan code glosses. Sementara itu interactional metadiscourse terdiri dari booseters, edges, attitude markers, self mentions dan engangement markers. Studi ini juga mengungkapkan bahwa penanda transition marker adalah yang tertinggi pada siswa perempuan karena kebanyakan para siswa perempuan belajar di luar kelas seperti di pondok pesantren. How to Cite: Suhono, Haikal.(2018). Interactive Metadiscourse and Interactional Metadiscourse Categories ff Students’ International Program School Based on Gender. IJEE (Indonesian Journal of English Education), 5(1), 81-91. doi:10.15408/ijee.v5i1.5505